2022
DOI: 10.2174/1381612828666220902124856
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic-hydrophilic Alternation: An effective Pattern to de novo Designed Antimicrobial Peptides

Abstract: The antimicrobial peptide (AMP) is a class of molecules that are active against a variety of microorganisms, from bacterial and cancer cells to fungi. Most AMPs are natural products, as part of an organism's own defense system against harmful microbes. However, the growing prevalence of drug resistance has forced researchers to design more promising engineered antimicrobial agents. Inspired by the amphiphilic detergents, the hydrophobic-hydrophilic alternation pattern was considered to be a simple but effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 107 publications
1
7
0
Order By: Relevance
“…flavus, as evidenced by reduced MIC values (Table ). This structural transformation is pivotal and aligns with the well-established theoretical models of AMP actions on cellular membranes . The engineered AMP CecXJ-37N exhibits an 11-fold increase in the α-helix ratio compared to the nonamidated isomer in a comparable environment at the prokaryotic membrane, showing a smaller MIC .…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…flavus, as evidenced by reduced MIC values (Table ). This structural transformation is pivotal and aligns with the well-established theoretical models of AMP actions on cellular membranes . The engineered AMP CecXJ-37N exhibits an 11-fold increase in the α-helix ratio compared to the nonamidated isomer in a comparable environment at the prokaryotic membrane, showing a smaller MIC .…”
Section: Resultssupporting
confidence: 74%
“…This structural transformation is pivotal and aligns with the well-established theoretical models of AMP actions on cellular membranes. 29 The engineered AMP CecXJ-37N exhibits an 11-fold increase in the α-helix ratio compared to the nonamidated isomer in a comparable environment at the prokaryotic membrane, showing a smaller MIC. 30 The stepwise arrangement, orientation, and permeabilization mechanisms of AMPs, predominantly based on the activity of α-helical AMPs, have been conceptualized in five models.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Although the exact process is not yet fully defined, studies performed on model membranes (e.g., liposomes) have shown that the positive charge is responsible for the initial interaction with the negatively charged membrane of microorganisms, whereas the hydrophobic portion is responsible for their insertion into the lipid bilayer [ 20 ]. Consequently, achieving the right balance between the hydrophilic and hydrophobic domains is key in determining the specificity of action of AMPs [ 21 ]. The positioning on the surface of the membrane and/or the incorporation into the membrane causes the disruption of membrane integrity with pore formation or membrane permeabilization followed by osmotic shock and loss of homeostasis [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the amphipathic nature of many AMPs, characterized by spatially segregated hydrophobic and hydrophilic faces within their molecular structure ( Huan et al, 2020 ), is crucial for their antimicrobial activity. This amphipathicity enables insertions into microbial membranes while retaining solubility in aqueous environments ( Cheng & Zeng, 2022 ). Another key property of AMPs is their concise sequence length, typically ranging from 10 to 50 amino acid residues.…”
Section: Designing Antimicrobial Peptidesmentioning
confidence: 99%
“…For example, the incorporation of non-natural amino acids, cyclization, and alternative delivery strategies (i.e., nanoparticle formulation) can enhance the stability of AMPs. The cationic charge of peptides can also be enhanced by incorporating positively charged amino acids, such as Lys and Arg, to increase the affinity of AMPs to the altered negative microbial surface charges ( Cheng & Zeng, 2022 ). Combination therapy with two or more AMPs or with an AMP and an antibiotic can increase the killing efficacy and reduce the likelihood of resistance development ( Sheard et al, 2019 ).…”
Section: Current Status and Application Of Ampsmentioning
confidence: 99%